2018
DOI: 10.1007/978-981-13-1056-0_23
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Iris Biometrics in Automated Teller Machines for Enhanced User Authentication

Abstract: The ubiquitous Automatic Teller Machine that revolutionized the way monetary transactions are carried out the world over is currently riddled with several security challenges. Top on the list of these challenges are the thefts and frauds associated with the ever popular Personal Identification Number based automatic teller machines. A lot of suggestions and proposals have been made in recent times, on how to combat the menace of automatic teller machine frauds. Biometrics is one of the most promising tools tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The login process prevents hackers from breaking into the accounts or using the account without the owner's permission (Lee, 2018). In recent years, biometric technology (i.e., facial recognition) has been used at ATMs to reinforce security (Okokpujie et al, 2018).…”
Section: Automated Teller Machine (Atm)mentioning
confidence: 99%
“…The login process prevents hackers from breaking into the accounts or using the account without the owner's permission (Lee, 2018). In recent years, biometric technology (i.e., facial recognition) has been used at ATMs to reinforce security (Okokpujie et al, 2018).…”
Section: Automated Teller Machine (Atm)mentioning
confidence: 99%
“…Biometrics is one of the safest and most reliable ways of authentication as it is the characteristic of the user only. The most popular biometric methods used are finger scan [4], [5], retina scan [6], face scan [7], [8], keystroke dynamics [9], [10], etc. Finger scan is the most popular biometric being used in mobile phones.…”
Section: Introductionmentioning
confidence: 99%
“…Although, most Nigerian organisations are ill-equipped to mitigate malware threats, studies have shown that organisations cannot effectively mitigate botnet in isolation [5]. Both private and public organisations collaborate to fight botnet but the individuals and corporate entities in the private sector still remains the biggest victim of cybercrime [23][24][25]. Towards fighting against all forms of financial and cyber-crimes therefore EFCC was setup and empowered by Nigerian government to work hand in hand with the cybercrime Prevention Working Group to combat financial crimes.…”
Section: Best Practices and Incentivesmentioning
confidence: 99%